Model of Critical Success Factors (CSFs) Influencing Food Inspection Management in UAE - Abdulla Almahrooqi, Fahed Khamis; Arif, Sazelin; Zainudin, Mohamad Zahir (International Journal of Sustainable Construction Engineering and Technology, 2022)
Muslims abide by strict dietary regulations that specify that the foods must be Halal for the consumption by Muslims. Previous research has shown that there is no definite or appropriate model of Critical Success Factors (CSFs) related to halal food inspection. The success of a project is largely dependent on critical factors, which primarily track the project’s development from the ground up (Ahsen et al. 2021). As a result, this study employed a quantitative approach to formulate a structural model of success factors that halal food authorities can use to optimise their inspection model, with a focus on training and development. The factors that affect/influence halal food inspection management, particularly when dealing with packaged food and halal certificates were identified through literature work. Questionnaire survey was conducted to collect data that was used in the formulation of the model. The Critical Success Factors (CSFs) model, which was created, tested and validated using SEM-AMOS software. The model has seven constructs (independent variables) and one dependent variable of the management of halal food inspection, thus having seven hypotheses. It was discovered that five out of seven of the hypotheses are were supported. These findings aid in the discovery of new information to several parties like managers, employees with progressively less experience, and local and foreign halal food inspectors, as well as curriculum and infrastructure beliefs, and how these effects affect opportunities and motivation. The study contributes significantly to UAE and global research community.